Strategies of Local Communities in Maintaining the Existence of Kapau Rice as a Traditional Culinary Identity in the Contemporary Era (Case Study: Nagari Kapau, Tilatang Kamang Subdistrict, Agam Regency) - Latifa Annisa; Faishal Yasin; Erningsih Erningsih (Jurnal Mamangan, 2025)
This study explains the shift in consumption patterns among communities from traditional foods to fast food. The purpose of this study is to explain the strategies used by the Nagari Kapau community in preserving the traditional Nasi Kapau dish in an era of globalization and modernization, such as KFC, McDonald's, and others. Bourdieu's Habitus Theory explains the ability of communities to adapt to modernization. The research methodology uses a qualitative method with a descriptive approach. The results show that the community's strategies for preserving Nasi Kapau include (1) maintaining the authenticity of the recipe, (2) innovating and adapting to the modern era, utilizing social media and food service platforms as promotional tools, and (3) holding local cultural events. These efforts are carried out collectively by traders, families, and the local community as a form of social and cultural responsibility. Nasi Kapau has survived globalization thanks to the collective awareness of the community in preserving traditional cuisine through a combination of cultural preservation, innovation, and the use of technology. This strategy not only preserves local culture but also strengthens the social identity of the Minangkabau community in the modern era.